Organize and Supervise Resources in Multi-account of AWS - Haque, Israrul; Ali, Ashif (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing is an emerging technology. It allows the customer to run the application by provisioning on-demand resources. There are cloud providers like AWS who allows their customer to provision resources. Customer may provide access to the multiple users to enable them to run their workloads using different services like EC2, S3, RDS, etc. With the help of different services provided by AWS, we can reserve computer power, storage, etc. Amazon Web Services (AWS) allows the customer to assign tags on their resources. The tags also known as metadata can be used to organize and manage resources in cloud computing. Tagging the resources in multiple accounts of AWS cloud computing is subject to errors and additional efforts. Our goal is to design a solution to automatically assign the tag on the resources so that we can easily organize and supervise resources in multi-account of AWS.